Formulation of Folate-Modified Raltitrexed-Loaded Nanoparticles for Colorectal Cancer Theranostics - Justin G. Rosch; Allison N. DuRoss; Madeleine R. Landry; Conroy Sun (MDPI AG, 2020)
Multifunctional nanoparticles (NPs) that enable the imaging of drug delivery and facilitate cancer cell uptake are potentially powerful tools in tailoring oncologic treatments. Here we report the development of a layer-by-layer (LbL) formulation of folic acid (FA) and folate antimetabolites that have been well-established for enhanced tumor uptake and as potent chemotherapeutics, respectively. To investigate the uptake of LbL coated NPs, we deposited raltitrexed (RTX) or combined RTX-FA on fluorescent polystyrene NPs. The performance of these NP formulations was evaluated with CT26 murine colorectal cancer (CRC) cells in vitro and in vivo to examine both uptake and cytotoxicity against CRC. Fluorescence microscopy and flow cytometry indicated an increased accumulation of the coated NP formulations versus bare NPs. Ex vivo near-infrared (NIR) fluorescence imaging of major organs suggested the majority of NPs accumulated in the liver, which is typical of a majority of NP formulations. Imaging of the CRC tumors alone showed a higher average fluorescence from NPs accumulated in animals treated with the coated NPs, with the majority of RTX NP-treated animals showing the consistently-highest mean tumoral accumulation. Overall, these results contribute to the development of LbL formulations in CRC theranostic applications.